A Study on the Regioselective Acetylation of Flavonoid Aglycons Catalyzed by Immobilized Lipases. - Papanikolaou, Angelos; Chatzikonstantinou, Alexandra V; Fotiadou, Renia; Tsakni, Aliki; Houhoula, Dimitra; Polydera, Angeliki C; Pavlidis, Ioannis V; Stamatis, Haralambos (Biomolecules, 2024)
This study aimed to explore the capacity of immobilized lipases on the acetylation of six aglycon flavonoids, namely myricetin, quercetin, luteolin, naringenin, fisetin and morin. For this purpose, lipase B from Candida antarctica (CaLB) and lipase from Thermomyces lanuginosus (TLL) were immobilized onto the surface of ZnOFe nanoparticles derived from an aqueous olive leaf extract. Various factors affecting the conversion of substrates and the formation of monoesterified and diesterified products, such as the amount of biocatalyst and the molar ratio of the substrates and reaction solvents were investigated. Both CaLB and TLL-ZnOFe achieved 100% conversion yield of naringenin to naringenin acetate after 72 h of reaction time, while TLL-ZnOFe achieved higher conversion yields of quercetin, morin and fisetin (73, 85 and 72% respectively). Notably, CaLB-ZnOFe displayed significantly lower conversion yields for morin compared with TLL-ZnOFe. Molecular docking analysis was used to elucidate this discrepancy, and it was revealed that the position of the hydroxyl groups of the B ring on morin introduced hindrances on the active site of CaLB. Finally, selected flavonoid esters showed significantly higher antimicrobial activity compared with the original compound. This work indicated that these lipase-based nanobiocatalysts can be successfully applied to produce lipophilic derivatives of aglycon flavonoids with improved antimicrobial activity.